Common core achieve. Reading & writing : mastering essential test readiness skills. - McGraw-Hill Education (Firm) (Bothell, WA : McGraw-Hill Education, 2015)
"Common Core Achieve: Mastering Essential Test Readiness Skills is designed to help you learn or strengthen the skills you need when you take your high school equivalency test."--Page v.
Identify main ideas and details -- Analyze relationships within texts -- Interpret words in context -- Examine text structure -- Assess how point of view shapes informational text -- Evaluate textual evidence -- Analyze structure across texts.
Includes index.
Keywords: Reading comprehension -- Examinations -- Study guides; Reading comprehension -- Problems, exercises, etc; Reading (Secondary) -- Examinations, questions, etc. -- Study guides; English language -- Composition and exercises -- Examinations -- Study guides; Composition (Language arts) -- Examinations -- Study guides; English language -- Written English -- Problems, exercises, etc; High school equivalency examinations -- Study guides; Composition (Language arts) -- Examinations; English language -- Composition and exercises -- Examinations; English language -- Written English; High school equivalency examinations; Reading comprehension; Reading comprehension -- Examinations; Reading (Secondary); Examinations; Problems and exercises; Study guides; Problems and exercises; Study guides; Examinations